Persepsi Mahasiswa terhadap Komunikasi Politik Anies Baswedan di Twitter (Studi pada Mahasiswa FISIPOL UMA) - H. Andri; Dedi Sahputra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the influence of Anies Baswedan's political communication on social media Twitter on the perception of students of the Communication Studies Study Program, Faculty of Social and Political Sciences, University of Medan Area. Using a quantitative approach, this study collected data through a survey with a questionnaire instrument distributed to 89 active students who used Twitter and were exposed to Anies Baswedan's political messages. The data were analyzed by simple linear regression techniques and determination coefficient tests to test the relationship between political communication and student perception. The results of the study show that Anies Baswedan's political communication on Twitter has a significant influence on student perception, although there are high doubts regarding the effectiveness of the message conveyed. Factors such as communication style, clarity of message, and ability to form a political image are important elements in building a positive perception of students. This study also revealed that political dynamics and polarization on social media affect students' perception of political communication carried out by Anies Baswedan. These findings provide important insights into the role of social media in shaping public opinion in the digital era.